Combined Barker-M-Sequence Coded LFM for High-Performance Subarray-MIMO Radar Applications - Iqbal, Akhmad; Tahcfulloh, Syahfrizal; Antonius, Antonius; Juliannanda, Rizkyandi; Nurrahmansyah, Arya (Universitas Medan Area, 2026)
Subarray-Multiple-Input Multiple-Output (SMIMO) radar is an advanced technology that integrates the advantages of phased-array and MIMO radars to enhance target detection resolution. A key challenge in SMIMO implementation lies in improving velocity resolution without compromising spectral efficiency, while maintaining accurate target detection capability under high sidelobe levels and inter-channel interference. This study proposes a novel approach—Combined Barker-M-Sequence Coded LFM—in which the LFM signal is phase-modulated using a hybrid code formed by concatenating a Barker sequence (length 11) and an M-sequence (length 7). Simulation results show that the proposed signal achieves a Peak Sidelobe Ratio (PSLR) of −20.83 dB, significantly outperforming LFM-Barker (−8.45 dB) and LFM-M-sequence (−16.3 dB). It also delivers a velocity resolution of 0.95 m/s and a range resolution of 225 m, representing a 38% improvement over standard LFM. Moreover, under SNR = −5 dB, the system achieves a SINR gain of 4.7 dB relative to LFM-M-sequence. This approach enables more efficient waveform utilization in modern radar applications—such as air surveillance, military defense, and autonomous vehicles—particularly in challenging environments characterized by low SNR, multipath propagation, and high clutter.